Sourcebook of interactive practice exercises in mental health - L'Abate, Luciano; SpringerLink (Online service). (New York Springer, 2011)
As a primary or an adjunct mental health therapy, written practice exercises have proven an effective, low-cost way for clients to transfer gains made in therapy to the challenges of daily life and relationships. These interactive workbooks expand on earlier self-help and distance writing methods along a continuum of healing approaches, from the proactive and preventive to the therapeutic and rehabilitative. But despite their appeal, large-scale access to high-quality materials hasn't always been readily available until now. The Sourcebook of Interactive Practice Exercises in Mental Health gives professionals a library of replicable, evidence-based, clinically robust protocols and workbooks for a broad range of clinical and non-clinical conditions, suitable for individuals, couples, and families. Luciano L'Abate places practice exercises in the context of current mental health and technological advances, offering guidelines for administration, helpful case studies, and caveats for those new to this type of intervention, and features a wealth of complete protocols in these major areas: Psychological disorders from the DSM-IV, including depression, anxiety, phobias, and PTSD. Couple and family concerns, from intimacy to domestic violence to children?s adjustment to divorce. Lifelong learning: assertiveness, emotional competence, social skills, and more. Family support skills: preparation for marriage, parenthood, and adoption. Plus exercises derived from widely-used psychological tests (e.g., the Beck Depression Inventory, the MMPI), behavior lists, and others. Clinical psychologists, mental health professionals, and psychotherapists will find the Sourcebook of Interactive Practice Exercises in Mental Health a therapeutic treasure chest filled with new approaches to intractable issues or unreachable clients, new means of viewing typical problems, even new ways for talk therapy to work with words.
Dedication -- Foreword by Rubin Battino -- Acknowledgments -- Chapter 1. Background: Recent Advances in Mental Health Interventions -- Chapter 2. Computers and Internet -- Chapter 3. The Self-help Movement in Mental Health: From Passivity to Interactivity? -- Chapter 4. Growth in the Use of Between-Session Homework Assignments -- Chapter 5. Low-costs Approaches to Promote Physical and Mental health -- Chapter 6. Distance Writing and its Applications -- Chapter 7. The Role of Self-help Practice Exercises in Mental Health -- Chapter 8. The Dictionary in Mental Health Interventions -- Chapter 9. Selected Case Studies for Workbook Sections -- Chapter 10. Implications of Recent Advances in Mental Health Interventions -- Section 1: Individuals with Psychiatric Classification or Reason for Referral -- Section 2: Conflicting Children, Couples, and Families -- Section 3. Individual Life-long Learning -- Section 4: Life-long Learning for Couples and Families -- Section 5. Lists and Single- and Multiple-score Tests -- Appendices -- References.
Electronic reproduction.
Keywords: Self-help techniques; Mental illness -- Treatment; Counseling -- Methods -- Forms; Self Report -- Forms; Mental Disorders -- Therapy -- Forms; Psychotherapy -- Methods -- Forms; Electronic books